2020
DOI: 10.1088/2631-7990/aba17c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of materials in laser-assisted extreme manufacturing: Raman-based novel characterization

Abstract: Laser-assisted manufacturing (LAM) is a technique that performs machining of materials using a laser heating process. During the process, temperatures can rise above over 2000 °C. As a result, it is crucial to explore the thermal behavior of materials under such high temperatures to understand the physics behind LAM and provide feedback for manufacturing optimization. Raman spectroscopy, which is widely used for structure characterization, can provide a novel way to measure temperature during LAM. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…There are various methods to study defects in monolayer TMDC materials, including Raman and photoluminescence spectroscopy and transmission electron microscopy. , Among these methods, Raman spectroscopy is a simple yet delicate noninvasive method for identifying materials’ defects. The quantifiable information of the defect form, concentration, and distribution can be gained from much larger areas of samples using Raman spectroscopy .…”
Section: Resultsmentioning
confidence: 99%
“…There are various methods to study defects in monolayer TMDC materials, including Raman and photoluminescence spectroscopy and transmission electron microscopy. , Among these methods, Raman spectroscopy is a simple yet delicate noninvasive method for identifying materials’ defects. The quantifiable information of the defect form, concentration, and distribution can be gained from much larger areas of samples using Raman spectroscopy .…”
Section: Resultsmentioning
confidence: 99%
“…The stabilization of biostructures against thermal treatment is referred to as its thermal or structural stability. Spectroscopic techniques [34][35][36][37] have been used to measure the effect of several additives on the thermal stability of biostructures including sugars. Thermal stabilization is important in industries where thermostable enzymes are produced with advantages of longer enzyme shelf life and lowered risk of microbial contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Raman thermometry, as a powerful technique, is widely used in determining the local temperature of the material at the nanoscale. , As a noncontact and nondestructive method, it provides an alternative for fragile or small-sized material detection, which has been reported in many studies in thermal measurement. Xu et al demonstrated an approach to probe the temperature rise of the multiwalled carbon nanotubes placed on Au nanoparticles using Raman thermometry.…”
Section: Introductionmentioning
confidence: 99%